Deep fried death - Day, Maddie (Day, Maddie. Country store mysteries, 2024)
Preparing for Outhouse Race during the annual Abe Martin Festival on Memorial Day, country store and restaurant owner Robbie Jordan finds herself in hot water when someone tries to frame her for murder and must flush out a killer before everything goes down the toilet.